Design and development of energy-efficient mechanism for flapping-wing micro air vehicle - Chin, Yao Wei (2019)
Flapping-wing flight provides versatile maneuvers such as vertical takeoff, hover, glide, dash and rapid turn, which can be used for all types of aerial mission. However, only a few flapping-wing micro air vehicles (FWMAVs) can hover and there is no guide to designing FWMAV for hovering. Hovering is challenging because it requires a high lift, generated at high energetic costs. A hovering FWMAV incurs additional inertial power to accelerate/decelerate wings in reciprocation and friction loss in its complex transmission, which are comparable to the aerodynamic power expended to generate lift. Currently, FWMAV depends on powerful, efficient motors powered by large batteries to meet power demands. We propose to reduce the energetic costs instead by four scalable solutions: bio-inspired elastic hinges (springs) integrated in flapping mechanism to recover inertial power; lightweight flexible wings to reduce wing inertia while allowing passive rotation; bearing-supported transmissions to reduce friction; and the clap and fling of four large crisscrossing wings like an X (i.e. X-wing) to generate high lift at low disk loading (aerodynamically more efficient). Novel analytical models are developed to predict passive wing rotation, lift generation and energetic costs based on desired wing stroke kinematics for different wingspan. We developed three types of mechanism with energy-storing flexure hinges to match the inertial power accordingly at different scales, namely: a three-spring thoracic mechanism with non-linearly increasing stiffness for 100-mm wingspan; a two-spring bistable thoracic mechanism for 120-mm wingspan; and a single-spring mechanism for bat-sized 240-mm and 280-mm wingspan X-wings. Results showed that elastic wing hinges can help to save power input and accelerate wings to higher speeds. The 280-mm span X-wing carried control surfaces and actuators to demonstrate multi-modal flight. This X-wing has a gearbox with optimized speed reduction ratio to match motor loading at peak efficiency. Friction in the gearbox is minimized with bearings supporting the gear shafts. This X-wing generates a maximum thrust of 39.9g at efficiency as high as 7.2 g/W at 15.4Hz, which is 49% more efficient than that of a propeller direct-driven by the same motor (41 g maximum thrust, 4.81 g/W). This X-wing can hover indoor for at least 7mins, with a total body mass of 26.24 g including 5.29-g 200-mAh 3.7V LiPo battery. It is envisaged that the models and results here can help engineers to develop efficient FWMAV at different scales which can hover and be the next air vehicle of choice.